Effect of acid pre-conditioning and/or delayed light irradiation on enamel bond strength of three resin-modified glass ionomers - Khoroushi, Maryam (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Polymerization of resin-modified glass-ionomers (RMGIs) is mediated through two competing mechanisms: An acid-base reaction and a light-dependent resin polymerization. Furthermore, pre-conditioning with acid has resulted in an increase in enamel bond strength of some RMGIs. This in vitro study evaluated the effect of pre-conditioning and/or delayed irradiation on bond strength of three RMGIs to enamel. MATERIALS AND METHODS: In this in vitro study, 144 flat enamel surfaces of human molars were ground using consecutively finer abrasives up to 600-grit silicon carbide paper. Each surface was rinsed and gently air-dried (n =12). The RMGIs (Fuji II LC Improved; Ionolux and Vitremer) were bonded to enamel surfaces using the following protocols: Groups 1: Based on manufacturers’ instructions; Groups 2: Pre-conditioning with phosphoric acid for 30 s; groups 3: A 2-min delay in irradiation; groups 4: Pre-conditioning with acid for 30 s plus a 2-min delay in light activation. After 24-h storage at 37°C and 500 rounds of thermocycling, the samples underwent shear bond strength (SBS) test. Data was analyzed with 3-way ANOVA and Tukey HSD test (α =0.05). RESULTS: There were significant differences between the study groups (P < 0.001). Acid-pre-conditioning increased Fuji II LC SBS values; it significantly decreased SBS values of Vitremer but had no effect on SBS values of Ionolux. Ionolux and Vitremer exhibited decreased enamel bond strength after a delay in light activation (P < 0.05). A 2-min delay in light activation combined with acid pre-conditioning increased RMGI SBS values only for Fuji II LC. CONCLUSION: Within the limitations of the present study, the effect of acid pre-conditioning, delaying irradiation and both on enamel bond strength of RMGIs was material-dependent. Further investigations are recommended.